Effects of a New Patient Safety-Driven Oxytocin Dosing Protocol on Postpartum Hemorrhage - David S. McKenna; Kari Rudinsky; Jiri Sonek (Journal of Pregnancy)
Objective. To determine if there was an increase in postpartum (PP) hemorrhage after decreasing the PP oxytocin dose from 40 to 30 units. Study Design. Retrospective cohort study comparing 8 months before to 8 months after the change. PP day 1 hemoglobin was subtracted from admission hemoglobin. Mean change was compared by Student’s t-test. The best fit polynomial was analyzed for trends between the two time frames. Women who received blood transfusions were excluded. Results. 73/3564 (2.0%) women received blood transfusions in the pre group and 64/3295 (1.9%) women in the post group, P=0.8. Mean hemoglobin change ± standard deviation was 1.53±0.03 g/dL for pre versus 1.52±0.05 g/dL for post, P=0.68. 1003/3114 (32.2%) in the pre group had a hemoglobin decrease of ≥2 g/dL compared to 918/2895 (31.7%) in the post group, P=0.7. 261/3114 (8.4%) in the pre group had a hemoglobin decrease of ≥3 g/dL compared to 252/2895 (8.7%), P=0.7. There were no significant trends between the two time frames. Conclusion. The change in the dose of PP oxytocin did not result in an increase in postpartum hemorrhage or an increase in the need for blood transfusion.